Temperature dependence of NR1/NR2B NMDA receptor channels - Cais, O; Sedlacek, M; Horak, M; Dittert, I; Vyklicky, L (Neuroscience, 2008)
N-methyl-D-aspartate (NMDA) receptors are highly expressed in the CNS, mediate the slow component of excitatory transmission and play key roles in synaptic plasticity and excitotoxicity. These ligand-gated ion channels are heteromultimers composed of NR1 and NR2 subunits activated by glycine and glutamate. In this study, patch-clamp recordings were used to study the temperature sensitivity of recombinant NR1/NR2B receptors expressed in human embryonic kidney (HEK) 293 cells. Rate constants were assessed by fitting a six-state kinetic scheme to time courses of transient macroscopic currents induced by glutamate at 21.9-46.5 degrees C. Arrhenius transformation of the rate constants characterizing NMDA receptor channel activity indicates that the most sensitive were the rate constants of desensitization (temperature coefficient Q(10)=10.3), resensitization (Q(10)=4.6) and unbinding (Q(10)=3.6). Other rate constants and the amplitude of single-channel currents were less temperature sensitive. Deactivation of responses mediated by NR1/NR2B receptors after a brief application of glutamate was best fit by a double exponential function (tau(fast): Q(10)=3.7; tau(slow): Q(10)=2.7). From these data, we conclude that desensitization/resensitization of the NMDA receptor and glutamate unbinding are especially temperature sensitive and imply that at physiological temperatures the channel kinetics play an important role in determining amplitude and time course of NMDA receptor-mediated postsynaptic currents and these receptors mediated synaptic plasticity.
Keywords: ledviny; Electrophysiology; kyselina glutamová; Glutamic Acid; lidé; buněčné linie; gating iontového kanálu; Kidney; Ion Channel Gating; Temperature; Cell Line; statistické modely; In Vitro Techniques; transfekce; Kinetics; techniky in vitro; Humans; kinetika; Patch-Clamp Techniques; algoritmy; receptory N-methyl-D-aspartátu; metoda terčíkového zámku; Algorithms; teplota; elektrofyziologie; rekombinantní proteiny; Recombinant Proteins; Receptors, N-Methyl-D-Aspartate; Models, Statistical; Transfection